Investigating fire patterns and methods to improve its safety in the country\'s hospitals; A review study - Mahmoud Mirakbari; Maryam Ooshaksaraie; Maryam Daneshmand mehr; Hossein Amouzad Khalili; Seyed Ali Majidi (بیمارستان, 2020)
Introduction : A large number of hospitals and medical healthcare centers catch fire every year. Nowadays, one of the most significant challenges that hospital designers and health providers faced with is fire safety. This study conducted to determine a comprehensive model for fire safety in hospitals by reviewing related studies.